Chordoma: retrospective analysis of 24 cases - Lopes, Ademar; Rossi, Benedito Mauro; Silveira, Claudio Regis Sampaio; Alves, Antonio Correa (São Paulo Medical Journal, 1996)
INTRODUCTION: Chordoma is a rare and slow-growing tumor, with local aggressiveness and preferential localization in the vertebral column. OBJECTIVE: The main objective of this study is to evaluate natural history and results of treatment of chordomas. METHODOLOGY: This is a retrospective study from 1953 to 1993. MATERIAL AND METHODS: The age ranged from 2 to 86 years (mean=34.5). Twelve patients were male and 12 female. The localization of the tumor was: 20 in the sacral region, 3 in head and neck and one out of the spine. RESULTS: The treatment, alone or combined, was surgery, radiation therapy and chemotherapy. The survival rate for patients with lesions in the sacrum ranged from 4 to 119 months, since the date of the symptoms. The 5-year overall survival was 4.2%. CONCLUSION: Chordoma is a rare and slow growing tumor, with a very difficult approach by surgery due to its preferential location in the sacrum and poor therapeutic results with radiation therapy or chemotherapy, mainly in patients with advanced disease.